2018
DOI: 10.1039/c8ib00099a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macromolecular crowding on the kinetics of glycolytic enzymes and the behaviour of glycolysis in yeast

Abstract: Water is involved in all aspects of biological activity, both as a solvent and as a reactant. It is hypothesized that intracellular water is in a highly structured state due to the high concentrations of macromolecules in the cell and that this may change the activity of intracellular enzymes due to altered binding affinities and allosteric regulations. Here we first investigate the kinetics of two glycolytic enzymes in artificially crowded aqueous solutions and show that crowding does indeed change their kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…This has been substantiated by a large amount of experimental work performed in both in vitro and in vivo systems, suggesting that most of the intracellular water exists in a polarized state when the cell is in a resting state [18,19]. This view offers a reasonable explanation of our results on the oscillatory coupling between intracellular water relaxation (measured by the fluorescence response of a series of 6-acyl-2-(dimethylamino)naphtalene probes) and central metabolites (such as ATP) during glycolytic oscillations including its dependence on the integrity of the actin cytoskeleton [12,13,15]. For instance, using a mathematical model based on the Yang-Ling isotherm [22,23], which is grounded on the principles of the AIH, we were able to adequately reproduce the coupling between the oscillations of ATP and the intracellular water dynamics observed in our experiments [13,15].…”
Section: Brief Account Of Ling’s Association-induction Hypothesismentioning
confidence: 52%
See 4 more Smart Citations
“…This has been substantiated by a large amount of experimental work performed in both in vitro and in vivo systems, suggesting that most of the intracellular water exists in a polarized state when the cell is in a resting state [18,19]. This view offers a reasonable explanation of our results on the oscillatory coupling between intracellular water relaxation (measured by the fluorescence response of a series of 6-acyl-2-(dimethylamino)naphtalene probes) and central metabolites (such as ATP) during glycolytic oscillations including its dependence on the integrity of the actin cytoskeleton [12,13,15]. For instance, using a mathematical model based on the Yang-Ling isotherm [22,23], which is grounded on the principles of the AIH, we were able to adequately reproduce the coupling between the oscillations of ATP and the intracellular water dynamics observed in our experiments [13,15].…”
Section: Brief Account Of Ling’s Association-induction Hypothesismentioning
confidence: 52%
“…This view offers a reasonable explanation of our results on the oscillatory coupling between intracellular water relaxation (measured by the fluorescence response of a series of 6-acyl-2-(dimethylamino)naphtalene probes) and central metabolites (such as ATP) during glycolytic oscillations including its dependence on the integrity of the actin cytoskeleton [12,13,15]. For instance, using a mathematical model based on the Yang-Ling isotherm [22,23], which is grounded on the principles of the AIH, we were able to adequately reproduce the coupling between the oscillations of ATP and the intracellular water dynamics observed in our experiments [13,15]. We also found that the Yang-Ling isotherm was more reliable in describing the kinetics of glycolytic enzymes in crowded environments than classical models based on mass action kinetics such as Michaelis-Menten (MM) and Monod-Changeux-Wyman (MCW) [15].…”
Section: Brief Account Of Ling’s Association-induction Hypothesismentioning
confidence: 57%
See 3 more Smart Citations